Psychedelic-Assisted Psychotherapy—A Systematic Review of Associated Psychological Interventions - Cavarra, Mauro; Falzone, Alessandra; Ramaekers, Johannes G.; Kuypers, Kim P. C.; Mento, Carmela (Frontiers in Psychology, 2022)
Modern clinical research on psychedelics is generating interesting outcomes in a wide array of clinical conditions when psychedelic-assisted psychotherapy is delivered to appropriately screened participants and in controlled settings. Still, a number of patients relapse or are less responsive to such treatments. Individual and contextual factors (i.e., set and setting) seem to play a role in shaping the psychedelic experience and in determining clinical outcomes. These findings, coupled with data from literature on the effectiveness of psychotherapy, frame the therapeutic context as a potential moderator of clinical efficacy, highlighting the need to investigate how to functionally employ environmental and relational factors. In this review, we performed a structured search through two databases (i.e., PubMed/Medline and Scopus) to identify records of clinical studies on psychedelics which used and described a structured associated psychotherapeutic intervention. The aim is to construct a picture of what models of psychedelic-assisted psychotherapy are currently adopted in clinical research and to report on their clinical outcomes. Ad-hoc and adapted therapeutic methods were identified. Common principles, points of divergence and future directions are highlighted and discussed with special attention toward therapeutic stance, degree of directiveness and the potential suggestive effects of information provided to patients.